Continued Fractions : Analytic Theory and Applications [ electronic resource ] - Jones, William B.; Thron, W. J. (Cambridge: Cambridge University Press, 2010)
This is an exposition of the analytic theory of continued fractions in the complex domain with emphasis on applications and computational methods
Keywords: Number Theory; Recreational Mathematics; Abstract Analysis; Mathematics; Electronic books